Price transmission for organic and conventional milk products in Sweden - Hanna Lindström (Institute of Retail Economics (HFI), 2021)
Although much empirical work addresses the efficiency of food supply chains by studying price transmission, studies on quality-differentiated food are scarce, and particularly for organic food vis-á-vis conventional food. This study adds to this scarce literature by analysing wholesale to retail price transmission for organic and conventional milk in the Swedish milk sector, using time-series analysis applied to monthly price data for the period Jan 2007–Nov 2017. Estimations are performed using the non-linear ARDL model which allows for asymmetric cointegration of prices and a simultaneous analysis of short- and long-run asymmetry, the latter of which has been largely overlooked in previous studies. In the case of conventional milk, results indicate positive asymmetries both in the short-run and the long-run. For organic milk, the long-run positive asymmetry is smaller and not statistically significant in all specifications. Organic consumers are therefore likely to experience smaller differences between surplus losses and gains, following positive and negative wholesale price changes, respectively.
Keywords: C22; L11; Q13; 330; Price transmission; organic food; non-linear ARDL